Pete the cat. Making new friends - Dean, Kim, 1969-; Dean, James, 1957- (Pete the cat., 2021)
"Secret agent Meow is on the case! When there is a mystery, no task is too big or too small for Pete the Cat, also known as Agent Meow. That's where the case of the lonely squirrel comes in. Pete the Cat is on a very important mission--helping Squirrel make new friends! Early readers will love following Agent Meow on this top-secret mission!"--Publisher description.